EFEKTIVITAS KONSELING KELOMPOK PENDEKATAN COGNITIVE BEHAVIOR THERAPY TERHADAP PERILAKU SIBLING RIVALRY SISWA SD NEGERI 3 SILIRAGUNG - Oky Faresa Ayu Kariyany; Heribertus Wicaksono; Raup Padillah (Program Studi Bimbingan dan Konseling, 2022)
The purpose of this research is to measure the effectiveness of using group counseling approach to Cognitive Behavior Therapy to reduce Sibling Rivalry behavior of students at SDN 3 Siliragung.The method in this research is descriptive using a quantitative approach. The variables in this study were group counseling with Cognitive Behavior Therapy and Sibling Rivalry approaches. Respondents in this study were 10 students who indicated experiencing Sibling Rivalry symptoms from the observations that had been made. Methods of data collection using the results of observations, questionnaires and interviews. The data processing technique uses the SPSS application. Based on the results of data analysis of research conducted at the State Elementary School 3 Siliragung on students